The origin of English language - Palacios, Sandra Janet (Logos Boletín Científico de la Escuela Preparatoria No. 2, 2025)
History of English language is an interesting topic. English belongs to the Indo-European family of languages. Proto-Indo-European was the first language used by nomads 5000 years ago. Then Germanic came from this ancestral speech. Throughout history we can distinguish three stages of the English language: Old English, Middle English and Modern English.